2011
DOI: 10.4314/ijest.v2i6.63711
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics analysis of a mixed flow pump impeller

Abstract: To improve the efficiency of mixed flow pump, Computational Fluid Dynamics (CFD) analysis is one of the advanced tools used in the pump industry. A detailed CFD analysis was done to predict the flow pattern inside the impeller which is an active pump component. From the results of CFD analysis, the velocity and pressure in the outlet of the impeller is predicted. CFD analyses are done using Star CCM+ software. These outlet flow conditions are used to calculate the efficiency of the impeller. The calculated val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…The increased outlet angle leads to smooth flow in exit region. [7] Figure 7. Head developed by the existing and modified impeller [7] The characteristic curve between discharge and overall efficiency is given in Fig .12.…”
Section: International Journal Of Advance Engineer Ing and Research Dmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased outlet angle leads to smooth flow in exit region. [7] Figure 7. Head developed by the existing and modified impeller [7] The characteristic curve between discharge and overall efficiency is given in Fig .12.…”
Section: International Journal Of Advance Engineer Ing and Research Dmentioning
confidence: 99%
“…[7] Figure 7. Head developed by the existing and modified impeller [7] The characteristic curve between discharge and overall efficiency is given in Fig .12. It shows that overall efficiency for the existing impeller starts decreasing after 11 lps.…”
Section: International Journal Of Advance Engineer Ing and Research Dmentioning
confidence: 99%
See 1 more Smart Citation
“…A vacuum pump is a device for creating, improving and/or maintaining a vacuum [1,2]Mechanical vacuum pumps works by the process of positive gas displacement, that is, during operation the pump periodically creates increasing and decreasing volumes to remove gases from the system, and exhaust them to the atmosphere [5]. Two basically distinct categories may be considered gas transfer pumps and entrapment or capture pumps [4].…”
Section: Introductionmentioning
confidence: 99%
“…as corrosion inhibitors in aqueous as well as acidic medium [4][5][6][7][8]. Studies also reported that the addition of Zn 2+ to the inhibitors brought a positive effect in the inhibition efficiency [9]. Literature supported the use of phthalic acid as a corrosion inhibitor in acidic as well as aqueous environment [10].…”
mentioning
confidence: 99%